BIBLIOMETRIC ANALYSIS OF GENDER EQUALITY AND EDUCATION QUALITY TO ACHIEVE SUSTAINABLE DEVELOPMENT GOALS (SDGS) IN 2030 - Andi Muhammad Farid Ramadhan; Fanesa Angeli; Rifqi Abror Ananda (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2024)
This article discusses international publication trends related to Gender Equality and Quality Education using the Scopus database. This study aims to determine publication trends based on region, publication subject, distribution of writings in various universities and opportunities for further researchers. Data collected by the author from search results in Scopus with the keywords Gender Equality, Quality Education and Sutainable Development Goals. Using bibliometric analysis through VOS Viewer Software to obtain publication linkage results. As a result, there are 90 articles published internationally from 2017 to 2023. Spain became a prolific country in the publication of international articles. Social Sciences is a subject of writing that is a lot in publishing articles. Some of the dominant keywords found in this publication are Sustainable Development Goal, gender disparity, quality of life, higher education, engineering education, entrepreneurship and the 2030 Agenda. Based on these results, this article becomes material for further researchers in developing international articles on Gender Equality and Quality Education towards the agenda of the Sutainable Development Goals in 2030